2005
DOI: 10.1177/1367877905055682
|View full text |Cite
|
Sign up to set email alerts
|

The moral imagination in primetime television

Abstract: In this article, we discuss how primetime programming is unjustly the subject of the moral panic constructed around television, a moral panic that seems primarily useful to maintain the high vs low culture dichotomy. To assess the moral content of primetime television, we used a framework derived from literary culture, since narratives’ content and morality (or, rather, [moral] imagination) are primarily discussed within this tradition. We will argue that primetime television (news, soap operas, sitcoms, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…We would suggest that serial drama, such as soap opera, is particularly relevant to studying the relationship between character morality and media, as soap operas frequently depict moral violations and issues of social concerns in the behaviors of their main characters, such as sexual activity (Greenberg & Busselle, ; Heintz‐Knowles, 1996; Kunkel, Cope, & Colvin, ), the consumption of alcohol and drugs (Furnham, Ingle, Gunter, & McClelland, ), and stereotyping (Greenberg & Brand, ). Despite the moral panic often surrounding the negative portrayals of character morality in soap opera, however, research suggests that the moral deliberations of characters often spark moral deliberations in viewers (Krijnen & Meijer, ), and thus may reify the social norms of the cultures they are part of (Mastro, Enriquez, Bowman, Prabhu, & Tamborini, ; Tamborini et al, ).…”
Section: The Model Of Intuitive Morality and Exemplarsmentioning
confidence: 99%
“…We would suggest that serial drama, such as soap opera, is particularly relevant to studying the relationship between character morality and media, as soap operas frequently depict moral violations and issues of social concerns in the behaviors of their main characters, such as sexual activity (Greenberg & Busselle, ; Heintz‐Knowles, 1996; Kunkel, Cope, & Colvin, ), the consumption of alcohol and drugs (Furnham, Ingle, Gunter, & McClelland, ), and stereotyping (Greenberg & Brand, ). Despite the moral panic often surrounding the negative portrayals of character morality in soap opera, however, research suggests that the moral deliberations of characters often spark moral deliberations in viewers (Krijnen & Meijer, ), and thus may reify the social norms of the cultures they are part of (Mastro, Enriquez, Bowman, Prabhu, & Tamborini, ; Tamborini et al, ).…”
Section: The Model Of Intuitive Morality and Exemplarsmentioning
confidence: 99%
“…Reflecting on moral values is a prevalent audience response to movies, partly because moral components are extensive in entertainment media (Krijnen & Meijer, 2005; Krijnen & Tan, 2009). Morally charged topics, such as sex and violence, are extensively depicted in top-grossing US films (Bleakley et al., 2012).…”
Section: Moral Reflection and Media Appraisalmentioning
confidence: 99%
“…Popular media can elicit an audience’s moral judgment due to inherent moral themes (Krijnen & Meijer, 2005) and the depiction of morally charged issues such as violence, crime, and sex (Bleakley et al, 2012). Through media exposure, audiences can learn what is right and wrong (Bandura, 1977), monitor character morality (Zillmann, 2000), and reflect upon their preexisting moral systems (Eden et al, 2014; Grizzard et al, 2017).…”
Section: Moral Reflection and Media Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Krijnen and Meijer (2005) found that television programmes (in the Netherlands) address a number of moral issues and see 'moral panics' as fuelled by and maintaining prejudice against 'low culture'. According to Gabb (1992), the rationale for censorship of television is to protect children from indecency.…”
mentioning
confidence: 99%